The fourth and fifth generations of African scholars: A South African case study - Madimabe Geoff Mapaya (Acta Academica, 2016)
In the so-called African millennium, it is perhaps excusable to pretend that African scholarship has come of age. Almost 20 years after the seminal article by Professor Thandika Mkandawire, which proffered a generational profile of the African scholar, it is perhaps opportune now to revisit the subject. Following on this historical masterpiece, the present article seeks to present a critique of what has become the hallmark of African scholarship albeit from a narrow South African perspective. It does so by taking into account some of the factors (good or bad) responsible for the status quo. A random sample of academic articles, including interviews with a number of African scholars, was used to formulate the argument in this article. A critique of the human capital in selected South African universities was also essential in completing a picture of academic progress or lack thereof. While not undermining the milestones reached, a kind of introspective reflection on the state of African scholarship can only aid the advancement of African knowledge enterprise; hence this instalment.